2018
DOI: 10.9740/mhc.2018.09.208
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of intramuscular olanzapine and benzodiazepines in agitated patients with mental illness

Abstract: Introduction:Intramuscular antipsychotics are commonly used to manage agitated patients. In 2005, Eli Lilly placed a warning on olanzapine's prescribing information following post-marketing reports of fatal drug reactions when intramuscular olanzapine was used in the setting of benzodiazepines. Data is lacking examining this drug combination.Methods:A medication use evaluation was conducted at a county psychiatric hospital surveying the usage of concomitant intramuscular olanzapine and lorazepam from October 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…TA B L E 3 Pharmacology for the agitated patients 11,35,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] 61 and document this in the electronic medical record where it is easily visible on the patient tracking board. A special wrist band is placed on the patient, and a sign is placed on their doorway to alert all healthcare workers of the violence risk.…”
Section: Implementation Of the Beta Guidelines: The Parkland Experiencementioning
confidence: 99%
“…TA B L E 3 Pharmacology for the agitated patients 11,35,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] 61 and document this in the electronic medical record where it is easily visible on the patient tracking board. A special wrist band is placed on the patient, and a sign is placed on their doorway to alert all healthcare workers of the violence risk.…”
Section: Implementation Of the Beta Guidelines: The Parkland Experiencementioning
confidence: 99%
“…18 Despite additional recent retrospective data suggesting the potential safety of this combination, current recommendations remain the same until higher-quality evidence is available. 2,18…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effect of the concomitant administration of parenteral benzodiazepines and IM olanzapine increases the risk of excessive sedation, cardiorespiratory depression, and mortality in some cases. 18 Postmarketing mortality data of 29 patients who received the combination was detailed by Marder et al 19 These reports ultimately led to the addition of FDA warnings against coadministration of IM olanzapine and benzodiazepines in the prescribing guidelines. 19 When examining these reports more closely, it is difficult to establish a cause and effect relationship between the combination of IM olanzapine and IM benzodiazepines with fatality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cases where benzodiazepines do not suffice or are contraindicated, it should be noted that a recent meta-analysis found that intramuscular olanzapine was less likely to be associated with QT prolongation than haloperidol, making it the agent of choice for management of SCRA-related behavioural disturbance where IM medication is required. 19 It is worth noting that where IM olanzapine is given to patients already receiving benzodiazepines, and although a recent analysis has highlighted a lack of data causally linking this combination with severe adverse effects, 20 careful monitoring to avoid respiratory depression is nevertheless probably prudent. Further work is certainly warranted to evaluate the actions of key SCRAs on determinants of ventricular repolarization and to explore interactions between cardiac effects of these drugs and commonly used medications, including psychotropic drugs and methadone.…”
mentioning
confidence: 99%